OPTIMIZING THE ROLE OF KPM STUDENTS IN DEVELOPING CIAWIGAJAH VILLAGE THROUGH DIGITAL TRANSFORMATION WITH WEB PLATFORM - Solehudin; Farid Wajdi; Roihatul Jannah; Nur Azizah; Maily Dianah Mardiah; Erlina Oktafiyah; Lita Nurafifah; Anis Siti Annisa; Muhammad Agus Mauludin; Neneng Nur Asiyah; Muhammad Chabib; Villia Vitriarti; Dhea Nurkhalizah; Aji Mahendra; Zain Alimudin (Jurnal Abdisci, 2024)
Two critical innovations that support environmental sustainability and community empowerment are waste processing into alternative fuels and village digitalization through the Internet. Both innovations offer solutions to the problem of waste accumulation while reducing our dependence on fossil fuels. This technology converts organic and inorganic waste into usable energy, such as biogas or RDF. This method can produce cleaner energy sources and reduce greenhouse gas emissions. On the contrary, village digitization through web platforms is a strategic step in increasing access to information, services, and economic opportunities for rural communities. By using this platform, villages can develop local potential, improve the efficiency of public services, and encourage broader digital inclusion. This platform can meet many needs, including village administration management, promotion of local products, and further training and education. The combination of these two innovations demonstrates collaborative efforts to realize sustainable development that combines environmentally friendly technology solutions and digital community empowerment. The results are hoped to improve the quality of life, reduce unpleasant environmental effects, and accelerate economic transformation in rural areas